Interplay of discourse and syntax in the acquisition of German as a second language in childhood - Sopata, Aldona (Glottodidactica, 2021)
The goal of this study is to investigate the interplay of discourse and syntax, as it can be observed in the use of null objects, in the language development of a child who starts to acquire German at the age of nine years in a naturalistic setting. The study shows that children at such an age can profit from the knowledge already acquired in their first language. After nine months of exposure, the child under study uses null objects similarly to monolingual children. The acquisition of null objects in a second language can be impeded at an early stage, however, due to the different syntactic restraints for the use of null objects in the first and second languages.